Analysis of DNA methylation alterations in rice seeds induced by different doses of carbon-ion radiation. (18th July 2018) - Zhao, Qian; Wang, Wei; Gao, Shuai; Sun, Yeqing
Abstract: To investigate the mechanism underlying differences in biological effects induced by low- versus high-dose heavy-ion radiation (HIR) in rice plants, two-dimensional gel electrophoresis (2-DE) coupled with methylation-sensitive amplification polymorphism (MSAP) analysis were used to check the expression changes in rice leaf proteome profiles and the changes in DNA methylation after exposure of seeds to ground-based carbon-ion radiation at various cumulative doses (0, 0.01, 0.02, 0.1, 0.2, 1, 2, 5 or 20 Gy; 12 C 6+ ; energy, 165 MeV/u; mean linear energy transfer, 30 KeV/μm). In this study, principal component analysis (PCA) and gene ontology (GO) functional analysis of differentially expressed proteins of rice at tillering stage showed that proteins expressed in rice samples exposed to 0.01, 0.02, 0.1, 0.2 or 1 Gy differed from those exposed to 2, 5 or 20 Gy. Correspondingly, the proportion of hypermethylation was higher than that of hypomethylation at CG sites following low-dose HIR (LDR; 0.01, 0.2 or 1 Gy), whereas this was reversed at high-dose HIR (HDR; 2, 5 or 20 Gy). The hypomethylation changes tended to occur at CHG sites with both low- and high-dose HIR. Furthermore, sequencing of MSAP variant bands indicated that the plants might activate more metabolic processes and biosynthetic pathways on exposure to LDR, but activate stress resistance on exposure to HDR. This study showed that radiation induced different biological effects with low- and high-dose HIR, and that this may have been caused by different patterns of hyper- and hypomethylation at the CG sites.